2008
DOI: 10.1002/jclp.20496
|View full text |Cite
|
Sign up to set email alerts
|

Meditation with yoga, group therapy with hypnosis, and psychoeducation for long‐term depressed mood: a randomized pilot trial

Abstract: This randomized pilot study investigated the effects of meditation with yoga (and psychoeducation) versus group therapy with hypnosis (and psychoeducation) versus psychoeducation alone on diagnostic status and symptom levels among 46 individuals with long-term depressive disorders. Results indicate that significantly more meditation group participants experienced a remission than did controls at 9-month follow-up. Eight hypnosis group participants also experienced a remission, but the difference from controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 45 publications
1
130
1
1
Order By: Relevance
“…19 Yoga, an ancient mind-body discipline that continues to gain popularity throughout the Western industrialized world as both a recreational and therapeutic modality, 25,26 may offer particular promise for those suffering from RLS. Data from a growing number of controlled trials suggest that yoga can enhance mood [27][28][29][30] and sleep, 29,31,32 as well as decrease blood pressure 33 and improve glucose tolerance, [33][34][35] lipid profiles, 33,36,37 body composition, 33,37 and autonomic function, 34,36,37 factors associated with both RLS and CVD risk. 2,9,10,20 However, while mind-body therapies, including yoga, are often recommended for patients with RLS, 38,39 no clinical trials have yet examined the effects of yoga on RLS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…19 Yoga, an ancient mind-body discipline that continues to gain popularity throughout the Western industrialized world as both a recreational and therapeutic modality, 25,26 may offer particular promise for those suffering from RLS. Data from a growing number of controlled trials suggest that yoga can enhance mood [27][28][29][30] and sleep, 29,31,32 as well as decrease blood pressure 33 and improve glucose tolerance, [33][34][35] lipid profiles, 33,36,37 body composition, 33,37 and autonomic function, 34,36,37 factors associated with both RLS and CVD risk. 2,9,10,20 However, while mind-body therapies, including yoga, are often recommended for patients with RLS, 38,39 no clinical trials have yet examined the effects of yoga on RLS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and Anxiety being the leading problems for a home maker, Raja Yoga could be an effective method of treatment for Depression and Anxiety. Researchers conducted a pilot study to investigate the effects of meditation with yoga among 46 individuals with long term depressive disorder and found that there was not much of a difference in the depressive patients but it displayed a higher significance for treating low to high level depression [8]. Others in their review found encouraging results in the treatment of anxiety and depression through Yoga [9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, a growing body of research examined the impact of mindfulness meditation and other contemplative practices on a variety of human faculties related to attitudes and decision-making. The work began in the fields of health and stress management (Beddoe & Murphy, 2004;Davidson & Kabat-Zinn, 2003;Kabat-Zinn, 2005;Santorelli, 1999), expanded to psychology and psychotherapy (Germer, Siegel, & Fulton, 2005;Goleman, 2003;Langer, 1989;Langer, 2000) and also focused on education (Buchmann, 1988;Butler, Symons, Marshall, Kaufman, & Spiegel, 2008;Zajonc, 2003;Zajonc, 2008). Networks of educators and researchers now exist for promoting and researching the impact of mindfulness meditation and related practices in higher education (e.g., The Association for Contemplative Mind in Higher Education and the Mindfulness in Education network).…”
Section: Mindfulness Meditationmentioning
confidence: 99%